UNRAVELING THE DRIVERS OF JOB SATISFACTION AMONG BANK EMPLOYEES IN INDIA: A STUDY (International Journal of Food and Nutritional Sciences, 2021)
Job satisfaction reflects an individual's affective and emotional assessment of his or her work. Infact, it is the composite outcome of various attitudes of an employee towards different facets of job. Employees' satisfaction is contingent upon the various attitudes, both positive and negative, that an employee holds towards various facets of job. Job satisfaction is a multi-dimensional concept and is influenced by various psychological and environmental factors. The study of job satisfaction is very significant as employees spend a major portion of their life at work place. Moreover, job satisfaction has its impact on the general life of the employees because a satisfied employee is a contented and a happy human being also. The study makes an attempt to examine the degree of bank employees' satisfaction towards select organisational factors capable of influencing overall job satisfaction of employees working in the select branches of State Bank of India (SBI) in Cachar district of Assam. The degree of satisfaction of bank employees on select organisational factors capable of influencing job satisfaction has been analysed. The study also makes a comparative assessment of employees' satisfaction with respect to specific demographic variables. The study concludes that the employees serving in the branches of SBI in Cachar district of Assam are by and large satisfied with different facets of their job.